The LEGO ideas book - Dolan, Hannah; Hugo, Simon; Kosara, Tori, 1985-; March, Julia; Saunders, Catherine (Lego Ideas, 2022)
"Unlock your imagination with this colorful treasury of more than 200 new building ideas created by LEGO fan builders. Learn tips and tricks to become a better builder. Find out how professional LEGO designers get their ideas and meet the fan builders. Get inspired to make your own LEGO creations with ideas to build your dream home, create an alien sports center, design a time machine, grow your own brick-built rooftop garden, and much more. There is no limit when it comes to LEGO ideas. What will you build?"--